Optimizing Digital Technology and Innovation for SME Sustainability in the Digitalization Era: Lessons from Indonesia - Sulistyanto, Tri Hadi; Cahya, Willy Adi; Ismail, Asep Gopar; Idawati, Rd Nurvitasari (Journal of Sustainable Economic and Business, 2025)
Objectives: The goal of this paper is to explore lessons from existing literature on how technology and innovation can be used to help SMEs succeed in the digital age. By focusing on real-life experiences and practices from Indonesia, it aims to offer valuable insights that can guide the growth of more competitive and sustainable small businesses in an ever-changing global environment. Methodology: The method used in this research is a literature review of publications from 2020 to 2024 related to SMEs, sustainability, technology, and innovation, using the keywords SMEs, sustainability, technology, and innovation. The literature search was conducted using the Crossref, Google Scholar, Web of Science, and Scopus databases. The collected literature is then mapped using Visualization of Similarity Viewer online software. Finding: SMEs research in Indonesia increasingly focuses on external impacts and digital transformation strategies. Policies supporting sustainability, access to training, technology, and innovation are important for enhancing SMEs competitiveness. The strong link between technology, innovation, and digitalization confirms that optimizing digital technology helps SMEs survive and grow. Insights from Indonesia highlight the importance of digital transformation, training, policy implementation, and an innovation-driven ecosystem. Conclusion: Research on SMEs in Indonesia has been growing with a more specific focus on the impact of external factors and digital transformation strategies. The strong connection between technology, innovation, and digitalization can enhance SMEs’ competitiveness at both national and global levels.